(untitled) (Research, Society and Development, 2022)
Reverse Logistics, developed correctly, contributes to control in the emergence of new environmental conflicts. To this end, the construction of an action plan to prevent major environmental disasters from occurring can be a prosperous path for all. In this context, the present study aims to identify the perceptions about reverse logistics, of the population, of the municipality of Ijuí/RS, through a field research. The objective of this work is to enable the development of educational proposals to the community, aiming to alert the population about the importance of recognizing the Reverse Logistics process. Thus, the research will include the descriptive, bibliographic, explanatory research method, as well as a qualitative methodological approach, with the purpose of identifying the perception of the Ijuiense population, so that an environmental education proposal can be articulated, promoting sustainability, through responsible attitudes of citizens belonging to the municipality of Ijuí/RS. It is therefore concluded that environmental awareness on the issue of Reverse Logistics depends on the joint action of the whole society, and Environmental Education is a facilitating instrument for the construction of these strategies, which are indispensable for the promotion of a more just and sustainable planet.